Brain Mechanism of Acupuncture Treatment of Chronic Pain: An Individual-Level Positron Emission Tomography Study - Xu, Jin; Xie, Hongjun; Liu, Liying; Shen, Zhifu; Yang, Lu; Wei, Wei; Guo, Xiaoli; Liang, Fanrong; Yu, Siyi; Yang, Jie (Frontiers in Neurology, 2022)
Abstract Objective: Acupuncture has been shown to be effective in the treatment of chronic pain. However, there neural mechanism underlying the effective acupuncture response to chronic pain is still unclear. We investigated whether metabolic patterns in the pain matrix network might predict acupuncture therapy responses in patients with primary dysmenorrhea (PDM) using a machine learning-based multivariate pattern analysis (MVPA) on positron emission tomography data (PET). Methods: Forty-two patients with PDM were selected and randomized into two groups: real acupuncture and sham acupuncture (three menstrual cycles). Brain metabolic data from the three special brain networks (the sensorimotor network (SMN), default mode network (DMN), and salience network (SN)) was extracted at the individual level by using PetSurfer in 18F-FDG PET data. MVPA analysis based on metabolic network features was employed to predict the pain relief after treatment in the pooled group and real acupuncture treatment, separately. Results: Paired t-tests revealed significant alterations in pain intensity after real but not sham acupuncture treatment. Traditional mass-univariate correlations between brain metabolic and alterations in pain intensity were not significant. The MVPA results showed that the brain metabolic pattern in the DMN and SMN did predict the pain relief in the pooled group of patients with PDM (R2 = 0.25, P = 0.005). In addition, the metabolic pattern in the DMN could predict the pain relief after treatment in the real acupuncture treatment group (R2 = 0.40, P = 0.01). Conclusion: This study indicates that the individual level metabolic pattern in DMN associated with real acupuncture treatment response in chronic pain. The present findings advanced the knowledge of the brain mechanism of the acupuncture treatment in chronic pain.